The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1177/08830738060210100201
|View full text |Cite
|
Sign up to set email alerts
|

Acute Disseminated Encephalomyelitis in North Indian Children: Clinical Profile and Follow-Up

Abstract: Acute disseminated encephalomyelitis in children is not uncommon in developing countries, yet there is little systematic documentation of its clinical profile and follow-up. We studied the clinical and neuroradiologic features of acute disseminated encephalomyelitis in 52 consecutive children. Clinical details, magnetic resonance imaging (MRI) findings, and the results of other investigations were recorded, and children were followed up from 6 to 48 months. A repeat MRI was done after 3 to 4 months, and in tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 30 publications
4
22
0
Order By: Relevance
“…[245816] One difference noticed was the absence of optic neuritis in the present sample. Optic neuritis is reported to occur in 3-35% of cases in various reports.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…[245816] One difference noticed was the absence of optic neuritis in the present sample. Optic neuritis is reported to occur in 3-35% of cases in various reports.…”
Section: Discussionmentioning
confidence: 80%
“…Studies from India and abroad have reported that ADEM is more common in boys,[2489] while multiple sclerosis, the other demyelinating disorder with many similarities, is more common in women. [1011] The reason for this female preponderance in the present sample should be evaluated in view of the disproportionate increase in the incidence of multiple sclerosis in women in recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is characteristically monophasic and, when present, impaired consciousness is a helpful feature to help discriminate it from other demyelinating diseases such as MS. CC and other periventricular lesions in ADEM may be less common than that seen in MS or NMO, although the reported frequency is highly variable ranging from 5% to 80% in case series 36–42. When the CC is involved in ADEM, there is often a high overall lesion load and lesions may be large and extend into the CC from the adjacent white matter 42. Among 12 patients with ADEM and CC involvement, the CC was involved bilaterally in all, with the splenium affected in 9 of the patients 43.…”
Section: Demyelinating Disordersmentioning
confidence: 99%
“…Other recent publications also mention relapses of DEM [22][23][24] . A curious logical hiatus occurs when changing the diagnosis from DEM to MS after a recurrence, since the MRI lesion(s) is/are still atypical and similar to those of DEM.…”
Section: Recurrent Dem and Msmentioning
confidence: 99%